Моделювання фотонно-кристалічного хвилеводу - Кульбашник, М. О. (ХНУРЕ, 2024)
The purpose of this work is to explain the principles and methodologies for numerical modeling of photonic crystal waveguides. It explores the fundamental properties, design considerations, and modeling techniques needed to understand and optimize the behavior of light in these nanostructured waveguides and different waveguide bends. Operation characteristics of the photonic crystal waveguide bend have been numerically calculated within the framework of two dimensional model
Keywords: фотонно-кристалічний хвилевід